Double-blinded prospective randomized clinical trial in knee joint osteoarthritis treatment: safety assessment and performance of trehalose hyaluronic acid versus standard infiltrative therapy based on medium-weight sodium hyaluronate - Alberto Gobbi; Macarena Morales; Giulia Avio; Riccardo D'Ambrosi (Elsevier, 2022)
Introduction: Newly formulated trehalose-hyaluronic acid (T-HA) has proven to be more stable in vitro to the effects of hyaluronidase enzyme. Objectives: To compare clinical outcomes of T-HA with standard non-trehalose (NT-HA) hyal-uronic acid when administered as infiltrative therapy in patients with symptomatic osteoarthritis of the knee. Methods: A prospective controlled trial with parallel arms was performed. Sixty patients with persistent symptomatic knee osteoarthritis were randomized to T-HA or non-trehalose-hyaluronic acid groups. Each patient received 3 doses of either of the products separated by 15 days, with a follow-up at 3 (T1) and 6 (T2) months. The study was blinded for participants, caregivers, and outcome assessors. Treatment performance was measured with the International Knee Documentation Committee (IKDC), Knee Injury and Osteoarthritis Outcome Score (KOOS), and Visual Analogue Scale (VAS) for pain outcome scores and was compared with basal scores and between groups. Results: Each group consisted of 30 patients; the mean age was 56.4 ± 15.6 years. At 3 months, IKDC, KOOS, and VAS improved for both groups (P < .05). At 6 months, group T-HA continued to improve IKDC, KOOS, and VAS (P < .05), while group NT-HA scores decreased (P < .05). IKDC increased to 66.98 (60.92-78.79) for T-HA, while it decreased to 59.77 (35.34-73.03) for NT-HA. Conclusions: Both T-HA and NT-THA are safe and effective for treating early osteoarthritis symptoms. T-HA provides a longer duration of symptom relief than NT-HA does. Further studies are needed to determine the total lasting effects of T-HA.